Evaluation of the safety of C-spine clearance by paramedics: design and methodology - Vaillancourt, Christian; Charette, Manya; Kasaboski, Ann; Maloney, Justin; Wells, George A; Stiell, Ian G (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Canadian Emergency Medical Services annually transport 1.3 million patients with potential neck injuries to local emergency departments. Less than 1% of those patients have a c-spine fracture and even less (0.5%) have a spinal cord injury. Most injuries occur before the arrival of paramedics, not during transport to the hospital, yet most patients are transported in ambulances immobilized. They stay fully immobilized until a bed is available, or until physician assessment and/or X-rays are complete. The prolonged immobilization is often unnecessary and adds to the burden of already overtaxed emergency medical services systems and crowded emergency departments. Methods/Design The goal of this study is to evaluate the safety and potential impact of an active strategy that allows paramedics to assess very low-risk trauma patients using a validated clinical decision rule, the Canadian C-Spine Rule, in order to determine the need for immobilization during transport to the emergency department. This cohort study will be conducted in Ottawa, Canada with one emergency medical service. Paramedics with this service participated in an earlier validation study of the Canadian C-Spine Rule. Three thousand consecutive, alert, stable adult trauma patients with a potential c-spine injury will be enrolled in the study and evaluated using the Canadian C-Spine Rule to determine the need for immobilization. The outcomes that will be assessed include measures of safety (numbers of missed fractures and serious adverse outcomes), measures of clinical impact (proportion of patients transported without immobilization, key time intervals) and performance of the Rule. Discussion Approximately 40% of all very low-risk trauma patients could be transported safely, without c-spine immobilization, if paramedics were empowered to make clinical decisions using the Canadian C-Spine Rule. This safety study is an essential step before allowing all paramedics across Canada to selectively immobilize trauma victims before transport. Once safety and potential impact are established, we intend to implement a multi-centre study to study actual impact. Trial Registration ClinicalTrials.gov NCT01188447